India's emerging connectivity with Southeast Asia: Progress and prospects - Prabir De (Asian Development Bank Institute (ADBI), 2014)
Connectivity is the key building block of convergence and cohesion in any regional integration initiative. Development of connectivity across any region - especially of transportation linkages, energy pipelines, and information and communication technology - contributes to integration by reducing transaction costs and facilitating intraregional trade and investment. The potential gains from closer connectivity between South Asia and Southeast Asia are no doubt large. India's regional integration with Southeast Asia has been advancing well and several projects are being implemented at present. India's regional connectivity with Southeast Asia has been evolving on two pillars: northeast India for multimodal and intermodal operations, and southern India for multimodal operations. This paper presents India's broad proposals on connectivity projects with Southeast Asia and policy recommendations to strengthen connectivity throughout Asia, in particular between India and the Association of Southeast Asian Nations. Enhancing connectivity between South and Southeast Asia is a multifaceted task that will require the implementation of strong policy initiatives. Development of connectivity in Southeast Asia and South Asia will bring significant opportunities for industrial development in India and trade potential with South and East Asian countries.
Keywords: F15; O24; 330; connectivity; transport; trade; south asia; southeast asia; regional integration; Governance; India